The intellectual significance of comedy and cynicism in Arab dramatic cinematic discourse: محمد اكرم عبد الجليل (Al-Academy, 2020)
The majority of the arts share a goal directed at employing art works for the purpose of conveying the intellectual and symbolic connotations in order to work on a directed message and to achieve expression and aesthetic, and highlights the cinematographic mediator who shares with the other media in the use of intellectual properties through its tools and works. Consciousness and establishment of multiple visions with different views to reveal the intellectual, aesthetic and expressive devices located opposite the advertiser to perform functions with goals that intellectually deduce, insights and ideas emerging within the general context of the drama narrative and highlights among the discourse operators the cinematographer, And the researcher started from the principle of definition and access to the phenomenon of artistic emerged in the discourse of cinematography through the narrative of dramatic events through the solutions of exit based on the expression of comical comedy that contribute to attract the attention of spectators, as this phenomenon is interesting in the mediator. This vision and the role of expressive drama, which is carried out through the techniques of solutions and artistic output to convey the meaning to the spectator and achieve aesthetic taste